The Learning of Pancasila Seen from the Perspective of Islam in Aceh: What Lessons Can Be Learned? - Iswadi Iswadi; Muhammad Shaleh Assingkily; Herinto Sidik Iriansyah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to reveal the learning of Pancasila based on Islam in Aceh. This study used a qualitative approach with a descriptive study method. The subjects of this study were principals and teachers of SDIT Madani Aceh Tenggara, principals, and teachers of SMP 3 Gayo Lues and the people of Central Aceh. The instruments used participant observation, in-depth interviews, and documentation studies. The data analysis technique used data reduction, data presentation, and verification to draw a conclusion. The validity of the research data was tested by data triangulation techniques. The results of this study showed that Pancasila learning which contains material for fostering religious, nationalist and integrity characters in the nation's children was in line with Islamic studies which provide educative physical and spiritual guidance. The people of Aceh who was identical with Islam were very appropriated to make learning Pancasila as an effort to maintain religious harmony, ethnic and cultural diversity and increase the sense of nationalism in students. Through this research, it is hoped that it will become a prototype in the practice of learning Pancasila based on Islam in other areas.